Edukasi kesehatan gigi untuk meningkatkan kebersihan gigi dan mulut murid SDN 33 Banda Aceh - Reca, Reca; Nuraskin, Cut Aja; Salfiyadi, Teuku; Rahayu, Eka Sri; Mardiah, Ainun; Febriani, Henny; Wirza, Wirza; Suryani, Linda; Dzaki, Muhammad Haikal (Politeknik Kesehatan Kemenkes Aceh, 2025)
Oral health is an important aspect of maintaining overall health, especially in elementary school-aged children. Lack of understanding about oral hygiene can lead to various dental health problems, such as caries and periodontal disease. This community service program aims to improve oral hygiene status through dental health education for students of SDN 33 Banda Aceh City and their parents. The method used was pre-test and post-test without control group with univariate analysis. The intervention included counseling, demonstration of proper tooth brushing, and examination of debris index and calculus index. Results showed significant improvements in parents' knowledge, attitudes, and practices towards their children's dental health. In addition, there was an improvement in children's oral hygiene status, with the proportion of the poor category decreasing from 45.7% to 5.7%, while the good category increased from 22.9% to 42.9%. This program proves that dental health education conducted in a direct and interactive manner can increase awareness and habits of maintaining oral hygiene. Therefore, similar educational programs need to be carried out in a sustainable manner with the support of schools and parents